Challenges and prospects of Nigeria's sustainable energy transition with lessons from other countries' experiences - Oludamilare Bode Adewuyi; Mark Kipngetich Kiptoo; Ayodeji Fisayo Afolayan; Theophilus Amara; Oluwatobi Idowu Alawode; Tomonobu Senjyu (Energy Reports, 2020)
Sustainable energy transition is generally understood as a concept of developing robust, effective and efficient energy sectors in a particular country or region without compromising the present and future socio-environmental security. In view of this, several countries have made remarkable efforts towards achieving this all-important objective in compliance with modern energy needs and supply requirements. Over half of the reported impoverished people globally reside in the sub-Saharan Africa (SSA) region and a sizeable portion of these people (up to 400 million) live in Nigeria, being the most populated country in Africa. The economic growth and social development of any nation depend remarkably on the sufficiency of its energy sector. Thus, the realization of the Sustainable Development Goals (SDGs) comes the year 2030, as projected by the united nations, in Nigeria and the entire SSA region depends heavily on energy. In this study, the importance of an equitable right to sustainable energy adoption in Nigeria and other countries in Africa towards meeting United Nations SDG's deadline has been succinctly discussed. The reform activities towards improving the energy sector of Nigeria are discussed and appropriate recommendations are made taking clues from other developing countries' successful energy transition efforts.
Keywords: 330; Alternative energy technologies; Renewable energy resources; Sustainable Development Goals (SDGs); Sustainable energy transition; Technical and socio-economic factors